Perbandingan Efektivitas Penghimpunan Dana Wakaf Melalui Uang Berbasis Online di Global Wakaf dan Dompet Dhuafa - Budi Setiadi; Siska Lis Sulistiani (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. The development of information technology, especially in the field of financial technology helps waqf institutions in the development of waqf findrising strategies, one of which is the existence of online waqf. Therefore it is necessary to optimize the collection of waqf funds based online, one of them with efficiency. The purpose of this study was to determine the level of effectiveness of the collection of waqf-based online waqf funds in Global Waqf and Dompet Dhuafa. The research method used is qualitative with the DEA method. The object of study is the waqf institutions in Global Waqf and Dompet Dhuafa in the form of financial statements of 2 institutions in the period 2016 - 2017, interviews and documentation. Research results based on the above discussion are as follows: (1), Global Waqf and Dompet Dhuafa have fulfilled the elements in raising funds. Both institutions have their respective strategies in collecting funds based on online (2). The level of effectiveness of collecting waqf funds online at Global Waqf and Dompet Dhuafa using the DEA method for the 2016-2017 period, in the 2016 Dompet Dhuafa and Global Waqf levels, the efficiency level has been reaching 100% or equal to 1. This shows that Dompet Dhuafa and Global waqf had maximum efficiency in that year. Figures at 0.0% to gain indicate the efficiency target is in accordance with the actual conditions and obtained achieved 100%. In 2017 Dompet Dhuafa has an efficiency level of 100% or equal to 1. While Global Waqf has decreased efficiency to 50% due to its value of less than 100%. The optimization of online waqf collection in 2017 at Global Waqf institutions experienced low efficiency in order to achieve perfect efficiency operational costs should be reduced by around 80%, while online waqf receipts must be increased to 49% of the actual total. Abstrak. Adanya perkembangan teknologi informasi khususnya di bidang financial technology membantu lembaga wakaf dalam perkembangan strategi findrising wakaf, salah satunya yaitu dengan adanya wakaf online. Oleh karena itu dibutuhkan optimalisasi penghimpunan dana wakaf berbasis online, salah satunya dengan efisiensi. Tujuan penelitian ini adalah untuk mengetahui tingkat efektivitas penghimpunan dana wakaf berbasis wakaf online di Global Wakaf dan Dompet Dhuafa. Metode Penelitian yang digunakan adalah kualitatif dengan metode DEA. Objek yang diteliti adalah lembaga wakaf di Global Wakaf dan Dompet Dhuafa berupa laporan keuangan 2 lembaga pada periode 2016 – 2017, wawancara dan dokumentasi. Hasil Penelitian berdasarkan pembahasan di atas sebagai berikut : (1), Global Wakaf dan Dompet Dhuafa sudah memenuhi unsur-unsur dalam penghimpunan dana. Kedua lembaga tersebut mempunyai strategi masing-masing dalam menghimpun dana yang berbasis online (2), Tingkat efektivitas penghimpunan dana wakaf online di Global Wakaf dan Dompet Dhuafa dengan metode DEA periode 2016-2017, di periode 2016 Dompet Dhuafa dan Global Wakaf tingkat efisiensi nya sudah mencapai 100% atau senilai dengan 1. Hal ini menunjukan Dompet Dhuafa dan Global wakaf sudah efisiensi secara maksimal di tahun tersebut. Angka pada pada to gain 0.0 % menunjukan target efisiensi sudah sesuai dengan kondisi aktual dan memperoleh achieved 100 %. Di tahun 2017 Dompet Dhuafa tingkat efisiensinya sudah mencapai 100% atau senilai dengan 1. Sedangkan Global Wakaf mengalami penurunan efisiensi menjadi 50 % dikarenakan nilainya yang kurang dari 100%. Optimalisasi penghimpunan wakaf online pada tahun 2017 pada lembaga Global wakaf mengalami efisiensi rendah agar mencapai efisiensi sempurna biaya operasional harus dikurangi sekitar 80 %, sedangkan penerimaan wakaf online harus dinaikan menjadi 49 % dari total actualnya.